Responses of community traits and soil characteristics of Achnatherum inebrians-type degraded grassland to grazing systems in alpine meadows on the Qinghai-Tibet Plateau - Chen, Yanzhu; Xu, Changlin; Ma, Kaikai; Hou, Qingqing; Yu, Xiaojun (Frontiers in Plant Science, 2023)
Scientific grazing management is of great significance for the ecological health and sustainable use of alpine meadows. To explore appropriate management methods of alpine grasslands of the Qinghai-Tibet Plateau degraded by Achnatherum inebrians (Hance) Keng ex Tzvele presence, we studied the effects of different grazing systems on the A. inebrians population, grassland vegetation community traits, soil characteristics and soil microbial community structure for cold-season grazing plus supplementary feeding pasture (CSF) and four-season open public pasture (FOP) in Tianzhu County, Gansu Province. Compared with FOP, the CSF site showed significantly inhibited reproduction of A. inebrians, especially the crown width, seed yield and number of reproductive branches per plant were as high as 50%, significantly increased the aboveground biomass of edible forage and soil water content by 57% and 43–55%, better soil nutrients, and significantly reduced soil bulk density by 10–29%. Different grazing systems affected the composition and diversity of soil microbial communities, with a greater effect on fungi than on bacterial flora. The most abundant phyla of bacteria and fungi were Proteobacteria and Ascomycota for CSF (by 30–38% and 24–28%)and for FOP (by 67–70% and 68–73%), and the relative abundance and species of bacterial and fungal genera were greater for CSF than FOP. The α-diversity indexes of fungi were improved, and the β-diversity of fungi was significant difference between CSF and FOP. However, the grazing utilization time was prolonged in FOP, which reduced the diversity and abundance of soil bacteria and increased soil spatial heterogeneity. The use of A. inebrians-type degraded grassland in the cold season, and as a winter supplementary feeding and resting ground, could effectively inhibit expansion of A. inebrians, promote edible forage growth, enhance grassland productivity and community stability, and improve soil structure. The results guide healthy and sustainable utilization of A. inebrians-type degraded grassland in the Qinghai-Tibet Plateau.